Antibody conjugated nanoparticles as a novel form of antibody drug conjugate chemotherapy. (December 2018) - Johnston, Michael C.; Scott, Christopher J.
Abstract : Antibody conjugated nanoparticles (ACNPs) represent a novel strategy for the development of therapies exploiting antibodies to augment the delivery of chemotherapy payloads. Following in the footsteps of the success of antibody drug conjugates (ADCs), ACNPs are only now reaching clinical evaluation. In this review we discuss the success of ADCs and explore the opportunities ACNPs offer, such as broad chemotherapy payload selection, high drug to antibody ratios and the ability to finely tailor drug release in comparison to ADCs. The ability of ACNPs to elicit increased avidity due to multivalent effects and the potential to use these modular platforms in immunotherapeutic approaches is also explored. Through addressing challenges that still remain in bringing these complex formulations to the clinic, ACNPs hold obvious potential for the treatment of a wide range of cancers and other diseases where selective targeting of drug agents is essential.